Knowledge, attitudes, and practices of gynecologic oncology nurses toward patient decision aids for fertility preservation: a cross-sectional study in Zhengzhou, China - Xiaoyu Han; Xiaoxue Li; Manman Li; Tian Tian; Kaige Shi; Yun Shi; Fengzhi Zhang (Frontiers in Public Health, 2026)
Introduction To investigate nurses’ knowledge, attitudes, and practices regarding patient decision aids for fertility preservation in gynecologic oncology departments and to evaluate the associated factors. Methods This cross-sectional study used a questionnaire survey and convenience sampling. A total of 201 nurses working in gynecologic oncology-related departments of tertiary first-class hospitals in Zhengzhou, China, were recruited. The questionnaire covered demographic information, knowledge of patient decision aids for fertility preservation, attitudes toward these aids, self-reported practice, and perceived barriers to their use. Data were analyzed using SPSS version 27.0. Results Nurses held positive attitudes toward fertility preservation decision aids, but their overall practice level was low. Only 52.8% of nurses frequently or always introduced the existence of these tools to patients; 56.2% never or rarely actively learned about them, and nearly half (49.8%) were unclear about the process for using them. Multiple linear regression analysis showed that reproductive specialist nurse status and years of work experience were independent positive predictors of knowledge scores, whereas an associate degree or below and nurse title were negative predictors. The title of associate chief nurse was positively associated with attitude scores; age and other professiona l titles had no significant predictive effects. Individual characteristics were not associated with practice scores. The main barriers were lack of operational knowledge and lack of training. Conclusion Nurses in gynecologic oncology-related departments need to improve their practice regarding fertility preservation decision aids practice, as positive attitudes were accompanied by relatively low reported practice levels. Bridging this gap requires standardized training, improved tool accessibility, and multifaceted efforts.